Corporate governance of audit firms: Assessing the usefulness of transparency reports in a Europe‐wide analysis. (10th May 2018) - La Rosa, Fabio; Caserio, Carlo; Bernini, Francesca
Abstract: Manuscript Type: Empirical Research Question/Issue: Based on both institutionalized agency theory and meso‐level theory, this study examines corporate governance disclosure in an audit firm's transparency report (TR) and whether more disclosure is associated with (a) the audit function of the country in which it is disclosed; (b) high levels of investor confidence in public interest entities (PIEs) shown in the portfolio of the audit firm; and (c) increased competition within the audit market. Research Findings/Insights: On the basis of content analysis, different measures of a corporate governance disclosure index (CGDI) are calculated for a sample of 122 auditing firms from 10 European countries over the period 2010–2012. Despite attempts at harmonizing audit practice across the EU, results confirm the role of institutional context in explaining differences among European countries. Moreover, while the CGDI reveals that the TR does improve investor confidence, no evidence was found that the new disclosure requirement unsettled audit market concentration. Theoretical/Academic Implications: Results support arguments of the institutionalized agency theory that audit firms' corporate governance disclosures depend on both firm‐ and country‐level factors. Moreover, the interplay between these macro and meso factors explains the information asymmetry reduction that exists between auditors and shareholders, thus improving micro‐level investor confidence. Practitioner/Policy Implications: The study provides an analysis of audit firm transparency based on the information disclosed in mandatory TRs. Policymakers and practitioners may benefit from the knowledge of items included in the TRs expected to impact on investor confidence. It also proposes the use of the TR for achieving market competition strategies, although it may be inefficient.